Tinjauan Pengaruh Suhu dan Massa Katalis Terhadap Yield Bio-Oil Hasil Pirolisis Ampas Tebu (Sugarcane Bagasse) - Oktaviani, Oktaviani; Bahri, Syaiful; Sunarno, Sunarno (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
Sugarcane bagasse, as lignocellulosic biomass waste, has great potential for producing bio-oil through pyrolysis, which is the process of converting biomass into bio-oil, biochar, and gas. However, the main challenge in bio-oil production is reducing oxygen content and improving its quality. Therefore, this study evaluates the effect of temperature and catalyst use on bio-oil yield from sugarcane bagasse pyrolysis. The method used was a literature review, collecting quantitative data from various relevant studies on sugarcane bagasse pyrolysis and its operational conditions. The results showed that a temperature of 500°C yielded the optimal bio-oil yield of 60.4%, with higher temperatures increasing calorific value but reducing oxygen content. Additionally, the use of a catalyst can reduce oxygen content and improve bio-oil quality. In conclusion, temperature and the selection of the appropriate catalyst play a key role in improving the quality and efficiency of bio-oil production from sugarcane bagasse, which can support efforts toward transitioning to more sustainable energy sources.